Tracking Adaptation in Livestock Systems (TAiLS) Tool - Njuguna, Lucy (2023)
Despite the recognition of the high vulnerability of rural communities to climate change, discussions on how to establish adaptation goals, how to measure them, and the corresponding financial mechanisms are predominantly top-down. To contribute to a session on the linkages between local and global scales in developing adaptation tracking frameworks, this presentation showcases the TAiLS tool which is designed for use by governments to track adaptation in the livestock sectors in Eastern Africa. The tool was developed with extensive input from livestock keepers, researchers, and government representatives. The session was part of the Adaptation Futures Conference that took place on October 2 - 6, 2023 in Montreal, Canada.